Dynamorphic legumes - Baharuddin, Mohd Nasir; Zamzuri, Azmir (University Putra Malaysia, 2012)
Basically, my approach is rooted from natural form of composition and improvisation. To compose in the medium of the artistic presentation, the works make temporality interactive. It creates a visual display which evolves dynamically over time, instead of a single static frame, or a preset filmic sequence. The works invoke cross-rhythm, the systematic interplay of contrasting rhythmic motions within a single metric scheme. It brings the operation of an artistic form to the context of browsing the scientific world of presentation. The works were presented in adaptive functional aspects that interconnected to the viewer into visual intuitive form which creates patterns of attention that organize our faculties of perception.